Predicting Genome Architecture: Challenges and Solutions - Belokopytova, Polina; Fishman, Veniamin (Frontiers in Genetics, 2021)
Genome architecture plays a pivotal role in gene regulation. Use of the high throughput methods for chromatin profiling and 3D-interactions mapping provided rich experimental datasets describing genome organization and dynamics. These data challenges development of new models and algorithms connecting genome architecture with epigenetic marks and predicting changes of chromatin interactions during normal development and in course of diseases. In this review, we describe how chromatin architecture could be reconstructed from epigenetic data using biophysical or statistical approaches. We discuss the applicability and limitations of these methods for understanding mechanisms underlying chromatin architecture and scoring effects of structural variations in human cells.